PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. TRIWIJAYA SARI DI TANGERANG SELATAN - Anjali Laila Jamil; Thamrin (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the influence of work discipline and job satisfaction on employee performance, to determine the influence of job satisfaction on employee performance, and to determine the influence of work discipline and job satisfaction on employee performance at company PT. Triwijaya Sari. The method used is a quantitative method using associative. The sampling technique used is saturated sampling using a sample of 92 respondents. Data analysis uses regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are that the work discipline variable (X1) has a relationship or influence level of 0.550 on employee performance (Y), from the hypothesis test obtained a calculated t value > t table, namely (8.219 > 1.986). This can be strengthened with a significant value of 0.000 < 0.05. Therefore, the hypothesis H0 is rejected and Ha is accepted, meaning that the test results show a positive and significant influence between work discipline on employee performance at PT. Triwijaya Sari. Job satisfaction (X2) has a positive and significant influence with a relationship or influence level of 3.477 on employee performance (Y). From the hypothesis testing, the t-count value is obtained > t-table, namely (3.477 > 1.986). This is supported by a significance value of 0.001 < 0.05, thus H0 is rejected and H2 is accepted. The hypothesis test shows that work discipline and job satisfaction have a positive and significant effect on employee performance, with a coefficient of determination of 59.3%, while the remaining 40.7% is influenced by other factors. Simultaneous hypothesis testing yielded a calculated F value > F table (54.354 > 3.099). This is further supported by a significant probability value of 0.000 < 0.05. Therefore, H0 is rejected and H3 is accepted, indicating a simultaneous positive and significant effect between work discipline and job satisfaction on employee performance at PT. Triwijaya Sari.